A Comparison of Dynamics in Two Models for the Spread of a Vector‐Borne Disease. Issue 2 (24th July 2014) - Græsbøll, K.; Sumner, T.; Enøe, C.; Christiansen, L. E.; Gubbins, S.
Summary: In 2007, bluetongue virus (BTV) was introduced to both Denmark (DK) and the United Kingdom (UK). For this reason, simulation models were built to predict scenarios for future incursions. The DK and UK models have a common description of within‐herd dynamics, but differ greatly in their descriptions of between‐herd spread, one using an explicit representation of vector dispersal, the other a transmission kernel. Here, we compare model predictions for the dynamics of bluetongue in the UK, based on the 2007 incursion and vaccination rollout in 2008. We demonstrate how an agent‐based model shows greater sensitivity to the level of vaccine uptake and has lower variability compared with a kernel‐based model. However, a model using a transmission kernel requires less detailed data and is often faster.